The Problem of the Surplus of Graduates from Technical and University Education and Their Employment in Private Work (A Field Study) (Journal of human and social sciences, 2022)
This study examines the problem of surplus graduates from university and technical education in Libya and their limited absorption in the labor market, particularly in the private sector. Despite the expansion of higher education institutions and the growing number of graduates, a mismatch persists between educational outputs and market needs, resulting in high unemployment rates among graduates. The research aims to identify the causes of this surplus, analyze the skills gap, and propose potential solutions through field data collected from private institutions in Benghazi. The findings highlight the need for aligning educational programs with labor market requirements, enhancing graduates’ skills in languages, communication, and technology, and promoting private sector employment as a sustainable path for human development.
Keywords: Education Outcomes; Labor Market; Graduates Inflation; Technical Education; Entrepreneurship